Translating and retranslating Italian cinema across time: Fellini in the UK and in the US (Altre Modernità, 2017)
When studying film translation from an historical perspective, it is essential to establish which films were watched by which audience with what kind of consequences (Bosma 2015: 40); to the debate, one should add ‘where’ and ‘when’, as the context obviously must be taken into account. In addition to that, the context – both in terms of space and time – in which the translations of these films have been produced, consumed, and received also plays a key role, not only in determining viewer’s habits and expectations, but also in trying to study from a different and possibly new perspective the traditional subtitling vs. dubbing debate